Sosialisasi Penggunaan Instrumen Identifikasi Kesulitan Belajar Spesifik Bidang Akademik pada Guru SDN YPK Kodeware - Chelsi Yuliana S (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2023)
This community service activity aims to provide understanding to teachers in order to identify students who have obstacles so they can get proper teaching in conveying subject matter. This service is carried out with three activities, namely 1) preparation, 2) lectures, questions and answers and demonstrations, 3) evaluation. Materials are compiled through Special Assistance Teacher manuals and other relevant references. The result of this service activity is that teachers know how to identify students in groups with specific learning difficulties, so that teachers can improve appropriate learning to overcome those who have specific learning difficulties.